Environmental Carrying Capacity of Tourist Attractions in Mangunan Forest Resort, Bantul Regency - Maria Imaculata Rahmawathy Idan Kewuren; Kaharuddin Kaharuddin; Lies Rahayu Wijayanti Faida (Universitas Gadjah Mada, 2026)
The growth of nature tourism at Mangunan Forest Resort in Bantul Regency has created challenges in balancing environmental sustainability with tourism activities. This study assessed tourism carrying capacity at three main destinations — Puncak Becici, Hutan Pinus Sari, and Seribu Batu Songgo Langit — using Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC). Ecological correction factors included herpetofauna diversity, slope, and soil erodibility, while tourist satisfaction was measured via Customer Satisfaction Index (CSI) from 100 respondents per site. All three attractions operated below their ECC limits, indicating sustainable current visitation. Hutan Pinus Sari had the highest ECC at 1,478 people/day (CSI 77.85%) due to a larger area, shorter stays, and higher herpetofauna diversity. Puncak Becici followed with 1,150 people/day (CSI 76.32%), supported by high turnover. Seribu Batu Songgo Langit had the lowest ECC at 597 people/day despite the highest CSI (80.52%), reflecting spatial and ecological constraints. The results highlighted a strong link between carrying capacity and tourist satisfaction. Integrating ecological parameters with CSI yields a more comprehensive assessment for sustainable, conservation-based tourism management in Mangunan Forest Resort.